Two early medieval timber buildings from Castle Hill, Peebles (Proceedings of the Society of Antiquaries of Scotland, 1981)
NT 248803. ?Twelth century ditches and postholes: 1, circular ?tower (12.4m external diameter); 2, squarish structure (5m sides) with corner gap and four internal ?roof-bearing supports. D F R/Ed